Influence of ultrasonic vibration on TiN coated biomedical TI-13Zr-13Nb alloy - Abdullah, Arman Shah (2015)
Biomedical grade of titanium alloys are prone to undergo degradation in body fluid environment. Surface coating such as Physical Vapor Deposition (PVD) can serve as one of the alternatives to minimize this issue. Past reports highlighted that coated PVD layer consists of pores, pin holes and columnar growth which act as channels for the aggressive medium to attack the substrate. Duplex and multilayer coatings seem able to address this issue at certain extent but at the expense of manufacturing time and cost. In the present work, the effect of ultrasonic vibration parameters on PVD-Titanium Nitride (TiN) coated Ti-13Zr-13Nb biomedical alloy was studied. Disk type samples were prepared and coated with TiN at various conditions: bias voltage (-125V), substrate temperature (100 to 300 ºC) and nitrogen gas flow rate (100 to 300 sccm). Ultrasonic vibration was then subsequently applied on extreme high and low conditions of TiN coated samples at two different frequencies (8 kHz, 16 kHz) and three set of exposure times (5 min, 8 min, 11 min). Encouraging results of PVD coating are observed on the samples coated at higher polarity of nitrogen gas flow rate (300 sccm) and substrate temperature (300 ºC) in terms of providing better surface morphology and roughness, coating thickness and adhesion strength. All TiN coated samples treated with ultrasonic vibration exhibit higher corrosion resistance than the untreated ones. Microstructure analysis under (Field Emission Scanning Electron Microscopy (FESEM) confirms that the higher ultrasonic frequency (16 kHz) and the longer exposure time (11 minutes) produce the most compact coating. It is believed that hammering effect from ultrasonic vibration reduces the micro channels’ size in the coating and thus decelerates the corrosion attack. Nano indentation test conducted on the ultrasonic treated samples provides a higher Hardness/Elasticity (H/E) ratio than untreated ones. This suggests that the ultrasonic vibration treated samples could also have a lower wear rate